The garden of saba: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This story narrates the tale of the prosperous kingdom of Saba, known for its beautiful gardens and abundant resources. It highlights the blessings of gratitude and the consequences of ingratitude, as the people eventually face challenges due to their disobedience to Allah. The story serves as a reminder of the importance of appreciation and the need to remain faithful amidst prosperity.